(3eNJUQ GdCZGfjs - (3CHhGdQHjY SdjeGf Hf GdSjO GdCcQe CHi eMeO Hf SjOfG CejQ GdeDefjfs; (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj,J (B356 (3g` s ((3eQGcT s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GddhM hGdbde CHj bWjaI GdeYjWI (B: (3YeQh Hf GdhdjO Hf YbHI Hf CHj eYjW s
(3BNQgG (B:s
(3jfJgi HJQLeI eOQL GdQjM YGeQ Hf GdeLfhf GdLQei hBNQ eG ajg (B: (3CYQaJ QSekG ef SejI HGddhi OQLJ Ydjg GdQjM HYOc aGSJhi ced GdSaQ GdChd jJdhg ai GdSaQ GdKGfi TYQ Hf YQjV s
(3GdfSNI HgG MhGTs
(3hQO GdYfhGf H` cX (B1 / 129s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278s
Keywords: (3GdCOHs